Pendirian Akidah Muḥyī Al-Dīn Al-Nawawī Dalam Polemik Ru'yah Allāh Berdasarkan Sharḥ Ṣaḥīḥ Muslim: Muḥyī Al-Dīn Al-Nawawī’s Position on the Polemic of Ru'yah Allāh Based on Sharḥ Ṣaḥīḥ Muslim - Saful Amin, Mohd Saiful Aqil Naim; Syed Abdul Rahman, Syed Mohammad Hilmi (Online Journal of Research in Islamic Studies, 2023)
Muḥyī al-Dīn Yaḥyā bin Sharaf al-Nawawī (d. 676 H) is a figure known for his expertise in fiqh and hadith. Among his masterpieces that are the focus of scholars and researchers is Sharḥ Ṣaḥīḥ Muslim, which is also considered the best Sharḥ Ṣaḥīḥ Muslim. Apart from the two fields of knowledge, one of the fields that he has mastered but that has not yet been widely highlighted is the field of islamic creed. Therefore, there is a need for a study of the character of this great scholar in the field of islamic creed. Among the issues and polemics of theology that are given attention by the theologians is the polemic of the ru’yah Allah and al-Nawawī also provides views on this polemic. Therefore, this study was written to analyze the stance of al-Nawawī and his position in the polemic of Allah's ru'yah in order to identify the stance of this hadith figure. This study uses the method of content analysis based on Sharḥ Ṣaḥīḥ Muslim as well as the works of scholars in the science of islamic creed to obtain relevant information. The study found that al-Nawawī's stance in this polemic is in line with the core essence and methodology of the creed brought by Ahl al-Sunnah wa al-Jamā'ah among al-Ashā'irah scholars who argue with evidence of revelation (naqlī) and logic (' aqlī). This at once proves that al-Ashā'irah scholars are also represented by the foremost hadith scholars and not just theologians.